Editorial Note (2024)
The editorial institutions of the Colombian Journal of Horticultural Sciences are pleased to communicate the recent entry into quartile 3 (Q3) of the SJR (Scimago), in the topics of Horticulture; Biochemistry, Genetics and Molecular Biology (miscellaneous); and Agricultural and Biological Sciences (miscellaneous). Performance indicators indicate that the Journal has an H-index of 7, SJR of 0.230, the highest number of citations received from Scopus journals, 105 and 113 for the years 2022 and 2023, the ratio of cited articles greater than 0.8 for windows 4 , 3 and 2 years of observation, increase in the number of cited articles (56 in 2022 and 61 by 2023), significant participation of female authors (>36% by 2023) and contribution of articles with the sustainable development goals, >12. The inclusion of the journal in Scopus allows the characterization of published articles, not only from its area of knowledge, but also from different public policy perspectives.